European agri-environmental policy and local institutions: A case study on French Regional Nature Parks - Mélanie Décamps (European Regional Science Association (ERSA), 2010)
Translating the European agro-environmental policy at a local scale implies costs of implementation, especially when a local cohesion is required. In the case of agro-environmental schemes (AES), farmers are supposed to contract individually and voluntarily but a territorial effect is expected. Then, the effectiveness of the policy depends on the coordination of the individuals' plans. In this paper, we assume that local institutions such as french 'Parcs Naturels Régionaux' can have a key role in this coordination. We suppose that their knowledge of the territory and their proximity with the local population allow them to adapt pertinently the policy. To address this issue empirically, we questioned 120 farmers about (i) the cost due to the contract and (ii) their perception of AES, both within and outside of three French 'Parcs Naturels Régionaux' (Morvan, Livradois-Forez et Volcans d'Auvergne). Then, using concepts from new institutional economics, we model the farmers' transaction costs and analyze how parks influence them, considering control variables. We also discuss how parks can restore farmers' confidence in the European policy.
Keywords: 330